Analysis of Internal Control Systems at The Office of The National Land Agency Sukabumi District - Fadhila, Ghina Rahayu; Nugroho, Gatot Wahyu; Sofiani, Venita (Adpebi International Journal of Multidisciplinary Sciences, 2023)
Internal control is to assess the effectiveness and efficiency of all activities whether they are by their objectives or not. If the internal control at the Office of the National Land Agency for Sukabumi Regency is very weak, then the possibility of errors that cause weak work effectiveness is also not good and vice versa, but such incidents can be minimized so that inefficiencies or ineffective performance can be identified quickly and corrective action (improvement) can be done as soon as possible because the internal control system has an important role in the organization. Internal Control System in Government Regulation No. 60 of 2008 which regulates government internal control and performance accountability reporting is also very necessary to know and measure the ability of a government agency to achieve the vision, mission, and goals of government agencies. This study aims to analyze and explain how the internal control system. This research was conducted using a qualitative descriptive method. Based on the results of the research, shows that the internal control system carried out at the Sukabumi Regency National Land Agency Office has gone well with the success of carrying out its duties in achieving goals and objectives determined in the 2021 performance report (LKj).